2018
DOI: 10.1136/bmj.j5855
|View full text |Cite|
|
Sign up to set email alerts
|

Low cigarette consumption and risk of coronary heart disease and stroke: meta-analysis of 141 cohort studies in 55 study reports

Abstract: ObjectiveTo use the relation between cigarette consumption and cardiovascular disease to quantify the risk of coronary heart disease and stroke for light smoking (one to five cigarettes/day).DesignSystematic review and meta-analysis.Data sourcesMedline 1946 to May 2015, with manual searches of references.Eligibility criteria for selecting studiesProspective cohort studies with at least 50 events, reporting hazard ratios or relative risks (both hereafter referred to as relative risk) compared with never smokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
304
1
32

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 483 publications
(357 citation statements)
references
References 112 publications
20
304
1
32
Order By: Relevance
“…While some dual users may have decreased the number of cigarettes they are smoking, these individuals are still exposing themselves to substantial risk. As noted above, a recent meta‐analysis found that even smoking one cigarette per day leads to 50% of the cardiovascular disease risk as smoking 20 cigarettes per day does 10 …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While some dual users may have decreased the number of cigarettes they are smoking, these individuals are still exposing themselves to substantial risk. As noted above, a recent meta‐analysis found that even smoking one cigarette per day leads to 50% of the cardiovascular disease risk as smoking 20 cigarettes per day does 10 …”
Section: Discussionmentioning
confidence: 87%
“…For instance, even if e‐cigarettes result in some individuals cutting down the amount of combustible tobacco cigarettes they consume, this may not achieve significant health benefits. A recent meta‐analysis of prospective cohort studies examining cardiovascular disease risk in light and moderate smokers found that smoking a single cigarette per day still carried half the risk of a cardiovascular event as smoking 20 cigarettes per day 10 . Clearly then, dual users are still exposing themselves to significant health risks.…”
mentioning
confidence: 99%
“…Perhaps it is time for a wider discourse and greater emphasis on the risks and links between smoking and CHD as documented in Hackshaw et al. 's recent meta‐analysis Hackshaw, Morris, Boniface, Jin‐Ling, and Milenković (). Davidson et al.…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic, as past research, while limited, suggests that RYO cigarettes do not have a significantly different level of risk to FM cigarettes, and that risk does not meaningfully change with the weight of tobacco per cigarette(Darrall and Figgins, 1998; Koszowski et al, 2014; Laugesen et al, 2009; Shahab et al, 2008; Shahab et al, 2009). Harm appears primarily to be determined by regularly smoking, and the number of years doing so, and to a much lesser extent, by the number of cigarettes smoked(Begh et al, 2015; Centers for Disease Control Prevention, 2010; Hackshaw et al, 2018). …”
Section: Introductionmentioning
confidence: 99%